2010
DOI: 10.1086/651611
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Clinical Trial of Fractional Doses of Inactivated Poliovirus Vaccine Administered Intradermally by Needle‐Free Device in Cuba

Abstract: This large-scale evaluation demonstrates the feasibility of fractional doses of IPV given intradermally as an antigen-sparing strategy but also shows that IPV given to infants at 6, 10, and 14 weeks of age results in suboptimal immunogenicity (especially for the fractional-dose arm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 28 publications
3
105
1
2
Order By: Relevance
“…Similarly, for polio booster immunization, intradermal 20% IPV dose resulted in either similar (6,13) or inferior (34,35) seroconversion rates in comparison to full intramuscular dose. However, intradermal immunization generally resulted in significantly lowered antibody titers (5,6,(31)(32)(33)(34)(35). These findings were seemingly not dependent on the intradermal immunization method used, because jet injectors (5,6,31,32,34,35), the Mantoux technique (4,35) or HMN arrays (13,33) evenly resulted in either similar or inferior results to full intramuscular dose.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, for polio booster immunization, intradermal 20% IPV dose resulted in either similar (6,13) or inferior (34,35) seroconversion rates in comparison to full intramuscular dose. However, intradermal immunization generally resulted in significantly lowered antibody titers (5,6,(31)(32)(33)(34)(35). These findings were seemingly not dependent on the intradermal immunization method used, because jet injectors (5,6,31,32,34,35), the Mantoux technique (4,35) or HMN arrays (13,33) evenly resulted in either similar or inferior results to full intramuscular dose.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, clinical trials in humans have been performed to investigate IPV dose sparing, by comparison of a 80% reduced IPV dose (20% of full dose) administered intradermally against a full IPV dose administered intramuscularly. For polio prime immunization in newborn infants, intradermal 20% IPV dose resulted in similar (4,5) or inferior (31)(32)(33) seroconversion rates compared to a full intramuscular dose. Similarly, for polio booster immunization, intradermal 20% IPV dose resulted in either similar (6,13) or inferior (34,35) seroconversion rates in comparison to full intramuscular dose.…”
Section: Discussionmentioning
confidence: 95%
“…10,11 Two recently published trials of intradermal delivery of reduced (20%) doses of inactivated poliovirus vaccines have reported contrasting results: one trial found that reduced intradermal doses administered to infants aged 2, 4 and 6 months induced similar rates of seroconversion but lower mean antibody titres, compared with intramuscular injection; 12 however a similar study administered the vaccine at 6, 10 and 14 weeks of age and observed inferior seroconversion rates with reduced intradermal doses. 13 Trials of intradermal immunization with seasonal and pandemic influenza vaccines have also been reported in the past year. Dose-sparing was not observed with a nonadjuvanted, subvirion H5N1 vaccine, 14 whereas a 60% intradermal dose of a trivalent seasonal flu vaccine resulted in similar immunogenicity as a standard dose delivered intramuscularly.…”
Section: Current Clinical Researchmentioning
confidence: 99%
“…The primary objective of these trials was to demonstrate non-inferiority of fractional (one-fifth) dose in terms of seroconversion for the ID route compared to the full dose via the IM route. Non-inferiority could not be demonstrated in the Cuban study; significantly lower seroconversion rates (ID: 52.9%, 85.0%, and 69.0% vs. IM: 89.3%, 95.5%, and 98.9% for serotypes 1, 2, and 3, respectively) and significant lower median antibody titers were induced in the ID arm after three doses of IPV [22]. In the Omani study, similar levels of seroconversion for serotypes 1 and 3 were after ID delivery of fractional doses and after IM vaccination of the full dose were detected.…”
Section: Jet Injectormentioning
confidence: 73%